Towards a comprehensive, person-centred assessment of health literacy: translation, cultural adaptation and psychometric test of the Dutch Health Literacy Questionnaire - Jany Rademakers; Geeke Waverijn; Mieke Rijken; Richard Osborne; Monique Heijmans (BMC, 2020)
Abstract Background Many health literacy instruments focus on reading skills, numeracy and/or information processing aspects only. In the Netherlands, as in other countries, the need for a comprehensive, person-centred measure of health literacy was observed and consequently the decision was made to translate the Health Literacy Questionnaire (HLQ) into Dutch. The HLQ has nine health literacy domains covering people's experiences and skills. This research sought to translate, culturally adapt and psychometrically test the HLQ. Methods The translation and adaptation was done using a systematic approach with forward translation guided by item intents, blind back translation, and a consensus meeting with the developer. The Dutch version of the HLQ was applied in a sample of non-hospitalized, chronically ill patients. Descriptive statistics were generated to describe mean, standard deviation and floor and ceiling effects for all items. A Confirmatory Factor Analysis (CFA) model was fitted to the data. Scores on the nine domains of the HLQ were compared across demographic and illness characteristics as a form of known-groups validity. Psychometric analyses included Cronbach's alpha, item-rest and item-remainder correlations. Results Using CFA, the Dutch HLQ psychometric structure was found to strongly align with the hypothesised (original) nine independent domains of the English version. The nine scales were found to be highly reliable (all scales had alpha between 0.83 and 0.94). Six of the nine HLQ-scales had items that show ceiling-effects. There were no ceiling effects present at the scale level. Scores on the scales of the HLQ differed according to demographic and illness characteristics: people who were older, lower educated and living alone and patients with multiple chronic diseases generally scored lower. Conclusions The Dutch version of the HLQ is a robust and reliable instrument that measures nine different domains of health literacy. The questionnaire was tested in a sample of chronically ill patients, and should be further tested in the general population as well as in different disease groups. The HLQ is a major addition to currently available instruments in the Netherlands, since it measures health literacy from a multi-dimensional perspective and builds on patients' experiences and skills.